RETRACTED: NFIL3 Facilitates Neutrophil Autophagy, Neutrophil Extracellular Trap Formation and Inflammation During Gout via REDD1-Dependent mTOR Inactivation - Tang, Honghu; Tan, Chunyu; Cao, Xue; Liu, Yi; Zhao, Hua; Liu, Yi; Zhao, Yi (Frontiers in Medicine, 2021)
Autophagy pathways play an important role in immunity and inflammation via pathogen clearance mechanisms mediated by immune cells, such as macrophages and neutrophils. In particular, autophagic activity is essential for the release of neutrophil extracellular traps (NETs), a distinct form of active neutrophil death. The current study set out to elucidate the mechanism of the NFIL3/REDD1/mTOR axis in neutrophil autophagy and NET formation during gout inflammation. Firstly, NFIL3 expression patterns were determined in the peripheral blood neutrophils of gout patients and monosodium urate (MSU)-treated neutrophils. Interactions between NFIL3 and REDD1 were identified. In addition, gain- or loss-of-function approaches were used to manipulate NFIL3 and REDD1 in both MSU-induced neutrophils and mice. The mechanism of NFIL3 in inflammation during gout was evaluated both in vivo and in vitro via measurement of cell autophagy, NET formation, MPO activity as well as levels of inflammatory factors. NFIL3 was highly-expressed in both peripheral blood neutrophils from gout patients and MSU-treated neutrophils. NFIL3 promoted the transcription of REDD1 by binding to its promoter. REDD1 augmented neutrophil autophagy and NET formation by inhibiting the mTOR pathway. In vivo experimental results further confirmed that silencing of NFIL3 reduced the inflammatory injury of acute gouty arthritis mice by inhibiting the neutrophil autophagy and NET formation, which was associated with down-regulation of REDD1 and activation of the mTOR pathway. Taken together, NFIL3 can aggravate the inflammatory reaction of gout by stimulating neutrophil autophagy and NET formation via REDD1/mTOR, highlighting NFIL3 as a potential therapeutic target for gout.